The voice of moderation in Islam : Malaysia as an exemplary nation - Shameem Abdul Jalil (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2014)
This study demonstrates where moderation and balance stand in the religion of Islam and how Malaysia, with her plural society, has since independence placed itself as an exemplary moderate Islamic nation. The work highlights the fact that Malaysia has always adopted a moderate position in the running of this multi-ethnic country, even before the word ―Wasatiyyah‖ had come into vogue in the country and the world. A mini questionnaire survey on moderation in Malaysia, conducted with 100 multiracial Malaysian professionals, revealed that 90% of the respondents confirmed their appreciation of Malaysia as an Islamic nation practicing moderation and the existence of religious freedom. The study unveils how the search for moderation in Malaysia has taken it through six phases, both at the macro and the micro levels, from phase 1: Seeding Moderation (1957-1971) to phase 6: Harvesting Moderation (2009 onward). Among the impact of this study is to look at how to protect, maintain and ensure that the voice of moderation, encouraged by Islam (as evident in the Quran and Hadith highlighted in this dissertation), continues in Malaysia. The attributes of moderation, as emphasized in this work, is applicable universally. This dissertation recommends that scholars use the principles highlighted in this study to mold a new generation of youth shaped by a stronger philosophy of moderation. The ultimate aim of this study is to promote moderation as a preferred lifestyle in our nation that can be emulated by the world.